Analisis Mengenai Keabsahan Akta Otentik Yang Dibuat Tidak Berdasarkan Kehendak Pihak Didalamnya (Studi Putusan No.621/Pdt.G/2019/PN.Sgr) - Kuntadi, Arnaz Adiguna; Dianti, Flora (Fakultas Syariah INSURI Ponorogo, 2023)
This research aims to determine the role of notary on creating Deed of Binding Sale and Purchase Agreement (PPJB) dan power of attorney to sell, it also analyze the validity of deeds that are made not based on the will of the party involved. This research uses the approach of case study and library research, which involves examining and colleting sources from journals, books and internet. The results of this research indicate that notary play an important role in creating authentic deeds, among the things that a notary must do is to provide legal counseling and act faithfully, honestly, diligently, independently, impartially, and to protect the interest of the parties involed, which stated on Article 15 Paragraph (2) letter (e) and Article 16 Paragraph (1) letter (a) of Law Number 2 Year 2014 concerning Amandments of Law Number 30 Year 2004 concerning Notary Position. The conclusion is that a deed that are made not based on the will of the parties, contain an elements of circumstances abuse (misbruik van omstandigheden), doesn’t meet the requirements as stated in Article 1320 and Article 1338 of the Civil Code can be invalidated in the court if it is proven to contain unlawful act.